Improving Students’ Understanding of Simple Present Tense Through Contextual Teaching at SMP Swasta GKPS 13 Sibarou - Damanik, Jerico Devaly; Sianturi, Erika; Silalahi, Rachel; Herman, Herman (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2025)
This community service initiative was undertaken with the express purpose of enhancing the comprehension of the Simple Present Tense among a cohort of Grade 7 students enrolled at SMP Swasta GKPS 13 Sibarou. The project directly confronted the prevalent grammatical hurdles students often encounter when endeavoring to construct grammatically sound sentences using the present tense. The pedagogical approach adopted for this endeavor was classroom-based instruction, meticulously designed around the principles of contextual learning. Data for this study was meticulously gathered from 20 Grade 7 students, employing a multifaceted collection strategy that included direct observation, the analysis of worksheets, and the administration of comprehensive written tests. The entire implementation process was systematically organized into three distinct phases: the preparation phase, which involved the meticulous design of instructional materials; the implementation phase, encompassing the actual delivery of learning activities; and the evaluation phase, characterized by the administration of post-tests and the collection of valuable feedback. The compelling outcomes of this project demonstrated a profound improvement: a remarkable 100% grammar accuracy, an encouraging 80% vocabulary usage, and an outstanding 100% sentence structure accuracy. These compelling results strongly indicate that contextual methods are remarkably effective in bolstering students’ grammatical proficiency. Consequently, the conclusion advocates for the systematic integration of Contextual Teaching and Learning (CTL) into routine instructional practices to foster superior learning outcomes.